The COVID-19 pandemic from Anatomic Pathology laboratories in Peru: La pandemia de la COVID-19 desde los laboratorios de anatomía patológica del Perú - Patiño-Calla, Karina (2021)
The anatomic pathology specialty plays a fundamental role within the multidisciplinary health systems team, since the majority of diseases are diagnosed by studying changes in cells, tissues and organs at both the macro and microscopic levels. Thus, this specialty is generally circumscribed in: surgical pathology, cytology and necropsy. Today, with the advent of new technologies in Peru, the practice of the specialty has considerably expanded its activity (immunohistochemistry, immunofluorescence, electron microscopy, molecular pathology, among others).